Performance evaluation of lightweight Crypto functions for Internet of things applications - Jaleel, Nubila; Habaebi, Mohamed Hadi; Islam, Md Rafiqul (Institute of Advanced Scientific Research, 2020)
Currently, the Internet of Things (IOT) and 5G technologies have gain huge popularity. The possibility for an object to communicate with others and to collect information about the environment enables a broad range of application markets. One of the main challenges in the IOT system is in the security and privacy of the generated data. The major issue in the design of a security system in IOT is in the device layer. This is due to the fact that the device layer consists of resource-constrained devices. The conventional cryptography methods, such for Advanced Encryption Standard (AES), Secure Hash Algorithm (SHA) and Rivest–Shamir–Adleman, (RSA), work well on systems which have reasonable processing power and memory capabilities. However, they do not work well with embedded systems and sensor networks. Thus lightweight cryptography methods are important. The lightweight (LW) crypto functions are designed for resource constrained devices with fixed block size and fixed permutation-based hash functions. The main LW crypto functions are Photon, Quark (QK), Spongent and Lesamnta. This paper compares between various LW crypto functions in terms of their power consumption, design, complexity and memory usage. In addition, the paper highlights the need for a new one-way hash function which supports variable transformation and variable block length size to suit several applications.